2015
DOI: 10.1093/ijnp/pyu036
|View full text |Cite
|
Sign up to set email alerts
|

Determining Pharmacological Selectivity of the Kappa Opioid Receptor Antagonist LY2456302 Using Pupillometry as a Translational Biomarker in Rat and Human

Abstract: Background:Selective kappa opioid receptor antagonism is a promising experimental strategy for the treatment of depression. The kappa opioid receptor antagonist, LY2456302, exhibits ~30-fold higher affinity for kappa opioid receptors over mu opioid receptors, which is the next closest identified pharmacology.Methods:Here, we determined kappa opioid receptor pharmacological selectivity of LY2456302 by assessing mu opioid receptor antagonism using translational pupillometry in rats and humans.Results:In rats, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 29 publications
(39 reference statements)
1
24
1
Order By: Relevance
“…Attenuation of the μ-opioid agonist activity of buprenorphine by samidorphan was shown by the pupillometry data, a physiological measure for studying the centrally mediated effects of opioids. 22 In the present study, BUP/SAM showed lower pupil constriction compared with that induced by buprenorphine alone, providing objective validation of the observed subjective outcomes.…”
Section: Discussionsupporting
confidence: 76%
“…Attenuation of the μ-opioid agonist activity of buprenorphine by samidorphan was shown by the pupillometry data, a physiological measure for studying the centrally mediated effects of opioids. 22 In the present study, BUP/SAM showed lower pupil constriction compared with that induced by buprenorphine alone, providing objective validation of the observed subjective outcomes.…”
Section: Discussionsupporting
confidence: 76%
“…In our selectivity experiments, we also saw modest blockade of our DAMGO induced effects at just 10 nM JNJ-67953964. While some MOR antagonism has been reported for this compound previously [25,40], we were surprised to detect it at this concentration, which did not achieve full KOR blockade in this preparation. Together, these observations indicate potentially important, unanticipated properties of JNJ-67953964.…”
Section: Discussioncontrasting
confidence: 55%
“…It was previously shown that LY2456302 had a 30-fold selectivity over MOR and DOR (Rorick-Kehn et al, 2014). To further assess any MOR activity, LY2456302 (4-60 mg) was orally administered to healthy humans to assess the effect on fentanyl-induced miosis in a previous pupillometry study (Rorick-Kehn et al, 2015). Doses of 25-60 mg yielded minimal to moderate MOR blockade, with no effect seen at 4 and 10 mg.…”
Section: Discussionmentioning
confidence: 99%